JARINGAN SARAF TIRUAN (NEURAL NETWORK) UNTUK ESTIMASI PRODUKTIVITAS PEKERJA KONSTRUKSI - LUTFAN ANAS ZAHIR; MOHAMMAD MUHLIS (JURNAL DAKTILITAS, 2022)
Abstract The development of the construction sector in Indonesia requires more effective approaches to improve productivity and efficiency. Estimating construction worker productivity, influenced by factors such as experience, education, and motivation, is often inaccurate with traditional methods. Neural Networks (Artificial Neural Networks) have emerged as a more advanced solution to enhance these estimations. This research analyzes Neural Network models and implements technology-based solutions to predict construction worker productivity. By utilizing the MLPRegressor model from scikit-learn and Neural Network models based on TensorFlow/Keras, this study aims to generate more accurate predictions. Initial results indicate that Neural Networks outperform traditional methods, achieving a Mean Squared Error (MSE) of 0.5 and an R² score of 0.85. The research also employs scipy.optimize methods to find the optimal combination of input variables, such as experience, motivation, and education, to meet specific productivity targets. This study provides a significant contribution to the application of machine learning techniques to improve the accuracy and efficiency of productivity estimation in the construction industry, while also paving the way for further development in optimizing worker performance. Keywords: Machine Learning, MLPRegressor Model, Neural Network, Productivity Estimation, TensorFlow Keras Abstrak Pembangunan sektor konstruksi di Indonesia membutuhkan pendekatan yang lebih efektif untuk meningkatkan produktivitas dan efisiensi. Estimasi produktivitas pekerja konstruksi, yang dipengaruhi oleh faktor-faktor seperti pengalaman, pendidikan, dan motivasi, sering kali tidak akurat dengan metode tradisional. Neural Network (Jaringan Saraf Tiruan) muncul sebagai solusi yang lebih canggih untuk memperbaiki estimasi ini. Penelitian ini menganalisis model Neural Network dan mengimplementasikan solusi berbasis teknologi tersebut untuk memperkirakan produktivitas pekerja konstruksi. Dengan memanfaatkan model MLPRegressor dari scikit-learn serta model Neural Network berbasis TensorFlow/Keras, penelitian ini bertujuan menghasilkan prediksi yang lebih akurat. Hasil awal menunjukkan bahwa Neural Network memberikan performa lebih baik, dengan Mean Squared Error (MSE) sebesar 0.5 dan R² score 0.85, dibandingkan dengan metode tradisional. Penelitian juga menggunakan metode scipy.optimize untuk menemukan kombinasi optimal dari variabel input seperti pengalaman, motivasi, dan pendidikan guna mencapai target produktivitas tertentu. Penelitian ini memberikan kontribusi penting dalam penerapan teknik machine learning untuk meningkatkan akurasi dan efisiensi estimasi produktivitas di industri konstruksi, serta membuka peluang pengembangan lebih lanjut untuk optimisasi kinerja pekerja. Kata kunci: Estimasi Produktivitas, Machine Learning, Model MLPRegressor, Neural Network, TensorFlow Keras